1 The Effectiveness of the Structured Numbered Head Learning Model on the Social Studies Learning Outcomes of Class V - Dwiyanti, Endang; Purnomo, Purnomo (Elementary School Teacher, 2020)
Based to the result, the observation and interview the low quality of education in Indonesia was caused by students' learning outcomes in some subjects were classified as low. This was supported by the data on social studies learning outcomes in the 5th grade students of elementary school of Kartini Cluster, Banjarnegara Regency, that were quite low. One of the reason was the teachers had not applied the appropriate learning model in accordance with educational regulations. The teachers used a teacher-centered learning model. The purpose of this study was to test the effectiveness of the Structured Numbered Heads model to result of social studies learning outcomes of 5th grade students of elementary school of Kartini Cluster, Banjarnegara Regency. This research used quantitative method with experiment design and nonequivalent control group design. The sample technique was cluster random sampling of 97 participantes. Data collection used test, observation and documentation. Hypothesis test result showed that tcountËƒttabel (5,8883 2,0003) which mean structured numbered heads model is was more effective to result of social studies learning outcomes of 5th grade students. The experiment class n-gain test result 0,4611 belong to medium criteria while control class n-gaint test result 0.481 belong to low criteria. The conclusion of this research is structured numbered heads was effective to be used in social studies learning material of 5th grade students of elementary school of Kartini Cluster, Banjarnegara Regency Data collection used test, observation and documentation. Hypothesis test result showed that tcountËƒttabel (5,8883 2,0003) which mean structured numbered heads model is was more effective to result of social studies learning outcomes of 5th grade students. The experiment class n-gain test result 0,4611 belong to medium criteria while control class n-gaint test result 0.481 belong to low criteria. The conclusion of this research is structured numbered heads was effective to be used in social studies learning material of 5th grade students of elementary school of Kartini Cluster, Banjarnegara Regency Data collection used test, observation and documentation. Hypothesis test result showed that tcountËƒttabel (5,8883 2,0003) which mean structured numbered heads model is was more effective to result of social studies learning outcomes of 5th grade students. The experiment class n-gain test result 0,4611 belong to medium criteria while control class n-gaint test result 0.481 belong to low criteria. The conclusion of this research is structured numbered heads was effective to be used in social studies learning material of 5th grade students of elementary school of Kartini Cluster, Banjarnegara Regency 0003) which mean structured numbered heads model is was more effective to result of social studies learning outcomes of 5th grade students. The experiment class n-gain test result 0,4611 belong to medium criteria while control class n-gaint test result 0.481 belong to low criteria. The conclusion of this research is structured numbered heads was effective to be used in social studies learning material of 5th grade students of elementary school of Kartini Cluster, Banjarnegara Regency 0003) which mean structured numbered heads model is was more effective to result of social studies learning outcomes of 5th grade students. The experiment class n-gain test result 0,4611 belong to medium criteria while control class n-gaint test result 0.481 belong to low criteria. The conclusion of this research is structured numbered heads was effective to be used in social studies learning material of 5th grade students of elementary school of Kartini Cluster, Banjarnegara Regency